Syntactic alignment and identification of theta-role subgroups in Mehináku stative verbs - de Felipe, Paulo Henrique (Revista do GEL, 2023)
In this work, I present a first analysis of the syntactic alignment in the Mehináku (Arawak) language to show how this language behaves in terms of its different verbal predicates and the arguments that these predicates take. I argue that this language tends to manifest an active-stative alignment (or split ergativity, as proposed by Aikhenvald (1999, 2001, 2002, 2018, 2019) for other Arawak languages), since it is the semantic type of the verb that determines which type of argument functioning as subject will be taken and, moreover, in what syntactic position this argument will appear. I show that transitive verbs, agentive intransitives, non-agentive intransitives, and most stative intransitive verbs (type 1) align in the same way, taking as subject one of the pronominal proclitics of the language positioned before the verb, while a small portion of the stative intransitive verbs (type 2) align with the direct object of the transitive verb since it takes as its subject the full pronouns of the language positioned after the verb. Furthermore, I show that the subject of the transitive verb (A) and the subjects of the agentive, non-agentive, and type 1 intransitive verbs are marked with the thematic role of agent or experiencer, while, in turn, the object of the transitive verb and the subject of the intransitive verb of type 2 (So) are marked with the thematic role of theme or patient.